Principles in the Management of Chronic Hepatitis B Viral Infection - Gerald Y Minuk (Canadian Journal of Gastroenterology)
Recently licensed and promising new experimental agents should have a profound impact on the treatment of patients with chronic hepatitis B virus (HBV) infection. However, certain management principles should remain unaltered. Recognizing the need for more urgent treatment in some individuals, being able to identify which patients require treatment and those who are most likely to respond to treatment, and selecting the optimal timing for treatment are clinical decisions that must continue to be addressed regardless of the antiviral agent ‘of the month’. This review outlines general principles and provides a generic, timeless approach to the management of patients with chronic HBV infection.